Конструкции с опорным глаголом в русском и итальянском языках / Support Verb Constructions. A Russian-Italian Contrastive Analysis - MAIKO, TATSIANA (Biblioteca di Studi Slavistici, 2022)
The monograph focuses on a special type of collocations-Support, or Light, Verb Constructions (SVCs). SVCs consist of a semantically reduced verb together with a noun (as the direct object or embedded in a prepositional phrase) that conveys core lexical meaning to the combination. SVCs often vary cross-linguistically, with languages using different strategies to conceptualize the same denotative situations. This study in line with the principles of the Integrated Contrastive Model, aims firstly to offer a corpus-driven contrastive cognitive-semantic description of SVCs in Russian and Italian based on the Construction Grammar model; and secondly to conduct a Contrastive Interlanguage Analysis of the use of Russian SVCs by Italian-speaking students. The findings of this study, in addition to its theoretical significance, may be useful in teaching Russian as a foreign language and could be of interest for lexicography.